Inverse Trigonometric Identities

Inverse trigonometric identities are mathematical relationships that involve the inverse trigonometric functions: arcsine (sin-1), arccosine (cos-1), arctangent (tan-1), arccosecant (cosec-1), arcsecant (sec-1), and arccotangent (cot-1). These functions determine the angles (or arcs) corresponding to given trigonometric ratios.

Here is the list of all the inverse trigonometric identities and their types. 

List

Basic Identities

A trigonometric function and its inverse cancel each other out, returning the original input within a specific range. These identities explain how trigonometric functions interact with their inverses.

  • sin-1(sin x) = x, for x ∈ ${\left[ -\dfrac{\pi }{2},\dfrac{\pi }{2}\right]}$
  • cos-1(cos x) = x, for x ∈ [0, π]
  • tan-1(tan x) = x, for x ∈ ${\left( -\dfrac{\pi }{2},\dfrac{\pi }{2}\right)}$

Similarly, for inverse functions applied to trigonometric values:

  • sin(sin-1(x)) = x, for x ∈ [-1, 1]
  • cos⁡(cos⁡-1(x)) = x, for x ∈ [-1, 1]
  • tan⁡(tan⁡-1(x)) = x, for x ∈ ℝ
  • cosec(cosec-1 x) = x, for -1 ≤ x ≤ ∞ or -∞ < x ≤ 1
  • sec(sec-1 x) = x, for 1 ≤ x ≤ ∞ or -∞ < x ≤ 1
  • cot(cot-1 x) = x, for -∞ < x < ∞

Negative Identities

Negative identities describe how inverse trigonometric functions behave when their input is negative. Some functions return a simple negation, while others involve a transformation using π:

For sine, tangent, and cosecant functions, a negative input results in the negation of the function’s value:

  • sin-1(-x) = -sin-1 x, for x ∈ [-1, 1]
  • tan-1(-x) = -tan-1 x, for x ∈ ℝ
  • cosec-1(-x) = -cosec-1 x, for |x| ≥ 1

For cosine, secant, and cotangent functions, the transformation involves subtracting the inverse function’s value from π, ensuring the result remains within the principal range:

  • cos-1(-x) = π – cos-1 x, for x ∈ [-1, 1]
  • sec-1(-x) = π – sec-1x, for |x| ≥ 1
  • cot-1(-x) = π – cot-1x, for x ∈ ℝ

Reciprocal Identities

Reciprocal identities establish direct relationships between inverse trigonometric functions and their reciprocal counterparts:

  • ${\sin ^{-1}\left( \dfrac{1}{x}\right) =\text{cosec}\, ^{-1}x}$, for x ≥ 1 or x ≤ -1
  • ${\cos ^{-1}\left( \dfrac{1}{x}\right) =\sec ^{-1}x}$, for x ≥ 1 or x ≤ -1
  • ${\tan ^{-1}\left( \dfrac{1}{x}\right) =\cot ^{-1}x}$, for x > 0

Complementary Identities

The sum of two complementary inverse trigonometric functions always results in a constant value of ${\dfrac{\pi }{2}}$:

  • sin-1 x + cos-1 x = ${\dfrac{\pi }{2}}$, for x ∈ [-1,1]
  • tan-1 x + cot-1 x = ${\dfrac{\pi }{2}}$, for x ∈ ℝ
  • cosec-1 x + sec-1 x = ${\dfrac{\pi }{2}}$, for |x| ≥ 1

Sum and Difference Identities

These identities are used where two inverse tangent functions are added or subtracted:

  • tan-1 x + tan-1 y = ${\tan ^{-1}\left( \dfrac{x+y}{1-xy}\right)}$, for xy < 1
  • tan-1 x – tan-1 y = ${\tan ^{-1}\left( \dfrac{x-y}{1+xy}\right)}$, for xy > -1

Double-Angle Identities

These relate inverse trigonometric functions to double angles:

  • 2 tan-1 x = ${\sin ^{-1}\left( \dfrac{2x}{1+x^{2}}\right)}$, for |x| ≤ 1
  • 2 tan-1 x = ${\cos ^{-1}\left( \dfrac{1-x^{2}}{1+x^{2}}\right)}$, for x ≥ 0
  • 2 tan-1 x = ${\tan ^{-1}\left( \dfrac{2x}{1-x^{2}}\right)}$, for -1 < x < 1

Here is a summary of all the identities.

We will now use the above identities to solve or simplify some expressions involving inverse trigonometric functions.

Simplify: sin-1 x – sin-1(-x)

Given, sin-1 x – sin-1(-x) …..(i)

First, we identify the identity which is needed to simplify the given expression. Here, we will use the negative identity of inverse sine functions.

As we know, sin-1(-x) = -sin-1 x

Here, from (i), we get

= sin-1 x – (-sin-1 x)

= sin-1 x + sin-1 x

= 2 sin-1 x

Evaluate: tan(tan-1 5)

Given, tan(tan-1 5) …..(i)

First, we identify the identity which is needed to simplify the given expression. Here, we will use the basic identity of inverse sine functions.

As we know, tan(tan-1 x) = x

Here, from (i), we get

= 5

Proofs 

Now, let us prove a few inverse trigonometric identities.

sin-1(sin x) = x

Let y = sin-1(sinx)

⇒ sin y = sin x

Since the range of the inverse sine function is ${\left[ -\dfrac{\pi }{2},\dfrac{\pi }{2}\right]}$, y must lie in this interval.

Thus, ${-\dfrac{\pi }{2}\leq y\leq \dfrac{\pi }{2}}$

⇒ y = x

⇒ sin-1(sinx) = x

Thus, sin-1(sin x) = x, for x ∈ ${\left[ -\dfrac{\pi }{2},\dfrac{\pi }{2}\right]}$

sin-1(-x) = -sin-1 x

Let sin-1(-x) = y

⇒ -x = sin y

⇒ x = -sin y

⇒ x = sin(-y)

⇒ sin-1 x = sin-1(sin(-y))

⇒ sin-1 x = -y

⇒ -sin-1 x = y

⇒ -sin-1 x = sin-1(-x)

Thus, sin-1(-x) = -sin-1 x, for x ∈ [-1, 1]

cos-1(-x) = π – cos-1 x

Let cos-1(-x) = y

⇒ -x = cos y 

⇒ x = -cos y

Since cos(π – q) = -cos q

⇒ x = cos(π – y)

⇒ cos-1 x = π – y

⇒ cos-1 x = π – cos-1(-x)

⇒ cos-1(-x) = π – cos-1 x

Thus, cos-1(-x) = π – cos-1 x, for x ∈ [-1, 1]

${\sin ^{-1}\left( \dfrac{1}{x}\right) =\text{cosec}\, ^{-1}x}$

Let cosec-1 x = y

⇒ x = cosec y

⇒ ${\dfrac{1}{x}=\sin y}$

⇒ ${\sin ^{-1}\left( \dfrac{1}{x}\right)}$ = y

⇒ ${\sin ^{-1}\left( \dfrac{1}{x}\right)}$ = ${\text{cosec}\, ^{-1}x}$

Thus, ${\sin ^{-1}\left( \dfrac{1}{x}\right) =\text{cosec}\, ^{-1}x}$, for x ≥ 1 or x ≤ -1

sin-1 x + cos-1 x = ${\dfrac{\pi }{2}}$

Let sin-1 x = y 

⇒ x = sin y

⇒ x = ${\cos \left( \dfrac{\pi }{2}-y\right)}$

⇒ cos-1 x = ${\cos ^{-1}\left( \cos \left( \dfrac{\pi }{2}-y\right) \right)}$

⇒ cos-1 x = ${\dfrac{\pi }{2}-y}$

⇒ cos-1 x = ${\dfrac{\pi }{2}}$ – sin-1 x

⇒ sin-1 x + cos-1 x = ${\dfrac{\pi }{2}}$

Thus, sin-1 x + cos-1 x = ${\dfrac{\pi }{2}}$, for x ∈ [-1, 1]

tan-1 x + tan-1 y = ${\tan ^{-1}\left( \dfrac{x+y}{1-xy}\right)}$

Let tan-1 x = A and tan-1 y = B

⇒ x = tan A and y = tan B

Since tan(A + B) = ${\dfrac{\tan A+\tan B}{1-\tan A\tan B}}$

⇒ tan(A + B) = ${\dfrac{x+y}{1-xy}}$

⇒ A + B = ${\tan ^{-1}\left( \dfrac{x+y}{1-xy}\right)}$

⇒ tan-1 x + tan-1 y = ${\tan ^{-1}\left( \dfrac{x+y}{1-xy}\right)}$

Thus, tan-1 x + tan-1 y = ${\tan ^{-1}\left( \dfrac{x+y}{1-xy}\right)}$, for xy < 1

2 tan-1 x = ${\sin ^{-1}\left( \dfrac{2x}{1+x^{2}}\right)}$

Let tan-1 x = y 

⇒ x = tan y

Now, R.H.S. = ${\sin ^{-1}\left( \dfrac{2x}{1+x^{2}}\right)}$

= ${\sin ^{-1}\left( \dfrac{2\tan y}{1+\tan ^{2}y}\right)}$

Since sin 2θ = ${\dfrac{2\tan \theta }{1+\tan ^{2}\theta }}$

= ${\sin ^{-1}\left( \sin 2y\right)}$

= 2y

= 2 tan-1 x = L.H.S.

Thus, 2 tan-1 x = ${\sin ^{-1}\left( \dfrac{2x}{1+x^{2}}\right)}$, for |x| ≤ 1

Solved Examples

Prove: tan1 1 + tan-1 2 = -tan-1 3

Solution:

As we know, the sum identity is: 
tan-1 x + tan-1 y = ${\tan ^{-1}\left( \dfrac{x+y}{1-xy}\right)}$, for xy < 1
Substituting x = 1 and y = 2, 
tan-1 1 + tan-1
= ${\tan ^{-1}\left( \dfrac{1+2}{1-1\times 2}\right)}$
= tan-1(-3)
= -tan-1 3

Prove: ${\cos ^{-1}x=\text{cosec}\, ^{-1}\dfrac{1}{\sqrt{1-x^{2}}}}$

Solution:

Let cos-1 x = y
⇒ x = cos y
Then, sin y = ${\sqrt{1-x^{2}}}$
⇒ cosec y = ${\dfrac{1}{\sqrt{1-x^{2}}}}$
⇒ y = ${\text{cosec}\, ^{-1}\dfrac{1}{\sqrt{1-x^{2}}}}$
Since y = cos-1 x
⇒ cos-1 x = ${\text{cosec}\, ^{-1}\dfrac{1}{\sqrt{1-x^{2}}}}$

Evaluate: sin(tan-1 3)

Solution:

Let y = tan-1
⇒ tan y = 3
Given, sin(tan-1 3)
= sin y
Since tan y = 3 = ${\dfrac{Opposite}{Adjacent}}$
Opposite = 3 and adjacent = 1
Thus, hypotenuse = ${\sqrt{3^{2}+1^{2}}}$ = ${\sqrt{10}}$
Here, sin y = ${\dfrac{Opposite}{Hypotenuse}}$ = ${\dfrac{3}{\sqrt{10}}}$
⇒ sin(tan-1 3) = ${\dfrac{3}{\sqrt{10}}}$

Solve for x: ${\tan ^{-1}\left( \dfrac{1-x}{1+x}\right) =\dfrac{1}{2}\tan ^{-1}x}$, x > 0

Solution:

Given, ${\tan ^{-1}\left( \dfrac{1-x}{1+x}\right) =\dfrac{1}{2}\tan ^{-1}x}$
Let tan-1 x = y
⇒ x = tan y
Rewriting the equation using substitution, 
${\tan ^{-1}\left( \dfrac{1-x}{1+x}\right) =\dfrac{1}{2}\theta}$
⇒ ${\tan \left( \tan ^{-1}\left( \dfrac{1-x}{1+x}\right) \right) =\tan \left( \dfrac{\theta }{2}\right)}$
⇒ ${\dfrac{1-x}{1+x}=\tan \left( \dfrac{\theta }{2}\right)}$
Since ${\tan \left( \dfrac{\theta }{2}\right) =\dfrac{\sin \theta }{1+\cos \theta }}$
Also, deriving from the triangle representation of tan y = x,
sin y = ${\dfrac{2x}{1+x^{2}}}$ and cos y = ${\dfrac{1-x^{2}}{1+x^{2}}}$
Here, ${\dfrac{1-x}{1+x}=\dfrac{\dfrac{2x}{1+x^{2}}}{1+\dfrac{1-x^{2}}{1+x^{2}}}}$
⇒ ${\dfrac{1-x}{1+x}=x}$
⇒ 1 – x = x + x2 
⇒ x2 + 2x – 1 = 0
⇒ x = ${\dfrac{-2\pm \sqrt{\left( 2\right) ^{2}-4\left( 1\right) \left( -1\right) }}{2\left( 1\right) }}$
⇒ x = ${-1\pm \sqrt{2}}$
Since x > 0
Thus, x = ${\sqrt{2}-1}$

Last modified on January 30th, 2025